Evaluating User Experience Satisfaction of LED Desk Lamp using FAHP-FCE Approach - Zhu, Minghui; Mohd Nazar, Ahmad Azahari; Rusman, Mohd Shahril; Abd Hamid, Linda (Environment-Behaviour Proceedings Journal, 2024)
Technology development has effectively guided the design and development of light-emitting diode (LED) desk lamps, and the design and development of desk lamps are closely related to users. However, studies on user satisfaction when using desk lamps are still under explored. To this end, this paper proposes a satisfaction evaluation method that combines the fuzzy analytic hierarchy process (FAHP) and fuzzy comprehensive evaluation (FCE). This research results could provide an effective theoretical and practical reference for the experience design of LED desk lamps to improve and meet users' needs, thereby potentially improving the design of LED desk lamps for better customer satisfaction.